The Trump phenomenon : how the politics of populism won in 2016 - Kivisto, Peter, 1948- (Bingley, U.K. : Emerald Publishing Limited, 2017)
On November 8, 2016, American voters surprised the world by electing a rank outsider with no previous political experience, businessman and celebrity Donald J. Trump, to become the 45th President of the United States after one of the most divisive and contentious campaigns in recent history. In this short book, Peter Kivisto analyses how this happened, focusing on who Trump is and the narratives about him and his candidacy that evolved during the campaign, who his supporters are and what their worldview is, and the role of the media, right-wing Christians, and the Republican Party in making Trump's victory possible. The Trump phenomenon must be viewed as a manifestation of right-wing populism, a movement which has serious implications for democratic values and practices, and this book examines how it took hold in America to put one of the most controversial presidents ever elected into the White House.
Includes index.
Includes bibliographical references.
Keywords: Presidents -- Election -- 20th century -- United States; Right and left (Political science) -- United States; Political culture -- United States; Political Science, American Government -- General; Politics & government